Pengaruh Pendidikan Kesehatan Tentang Deteksi Dini Perkembangan Anak Usia Balita Terhadap Peningkatan Pengetahuan dan Ketrampilan Ibu Dalam Melakukan Deteksi Dini Perkembangan Anak di Pusat Kesehatan Masyarakat Sikumana, Kota Kupang - Agustina Agustina; Mariana Oni Betan (JURNAL INFO KESEHATAN, 2017)
Early childhood is the "golden period" of child development, the window of opportunity and the critical period. This period is a sensitive period, a period of rapid and important growth and development. If there is a drift of growth and not detected early then it will affect the growth of the next flower (Siswanto, 2010). Based on data from East Nusa Tenggara Health Profile (2010), early detection in children under five in Kupang City was 1,506 children (9.3%) of 16,121 children under five. Research Ina A., 2014, in Kota Kupang, found 19 respondents experiencing development deviations. Existing phenomenon in the field rarely found early detection activities of child development in Maternal and Child Health Services. Assessment of progress with KPSP is easy to do as long as you know how. This study aims to analyze the influence of health education on early detection of the child under five development of children towards improving mother's knowledge and skill in early detection of child development, at Maternal and Child Health Services, health center of Sikumana, Kupang City ". This type of research is experimental with one group design pre-test and post-test design. The sample size was 44 people, ie 22 treatment and 22 no treatment. Random sampling. The results of this study indicate that there is an effect of health education on early detection of the development of children under five on improving mother's knowledge and skills in early detection of child development, in Maternal and Child Health Services Sikumana Health Center, Kupang City "with p = 0,000, for knowledge and p = 0,000 for skills.